Synchronization System Using Only One Delay-Locked Loop with Concatenated Code Sets in Optical-Wireless Code Shift Keying - Baba, Norito; Habuchi, Hiromasa; Komuro, Nobuyoshi (Journal of Signal Processing, 2025)
In optical-wireless code shift keying systems, the transmitted pseudo-noise (PN) code sequence fluctuates depending on the transmitted data, so it is a challenge to establish a simple synchronization method to maintain the synchronization timing of the PN code sequence. In this research, the synchronization system is simplified by concatenating modified pseudo-orthogonal M-sequence sets as a PN code sequence. In other words, the synchronization tracking system consists of only one delay-locked loop and a special reference concatenated code. The system performances in the single-user case and multi-user case are analyzed, and the impact of synchronization jitter on the error rate performance is examined. The results show that the impact of synchronization jitter on the error rate performance is not significant.